Comportamenti d'impresa e informazione del consumatore - Roberto Cellini; Guido Candela; Antonello Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
– The paper analyses the relationship between the average quantity of a good demanded by a consumer in a single act of purchase and the price setting behaviour of firms, in the presence of consumers' uncertainty about prices. A decrease of the average quantity purchased leads consumers to reduce the collection of information and increases the room for larger mark-up set by firms, with a consequent higher average price and higher variance of prices. An empirical analysis on the data about hotel stays in seaside resorts in Italy during the summer seasons in the period 1988-1997 is consistent with this point.
Keywords: 330